Species identity and spatial patterns of common oysters at oyster reefs of Guangdong, China - Zhou, Zihua; Qiu, Hong; Chen, Yaohui; Qiu, Jian-wen; Zhang, Yuehuan; Zhang, Jinghuai (Frontiers in Marine Science, 2025)
IntroductionAs concerns mount over the threats facing oyster reefs, awareness of the need to mitigate habitat loss and restore ecosystem services is increasing. However, challenges in identifying oysters have limited our understanding of their species- and population-level diversity, complicating efforts to establish effective marine protected areas. Therefore, this study aims to address these challenges by conducting a comprehensive survey along the coastline of Guangdong Province to assess the species composition and spatial distribution of oyster reefs across 51 intertidal sites, such as estuaries, islands, oyster farms, mudflats, and mangroves.MethodsIn total, we collected 742 oyster specimens by qualitative survey for oyster distribution and generated approximately 1,400 mitochondrial DNA sequences (N = 693 for 16S rRNA and N=706 for cytochrome c oxidase subunit I) to support genetic analysis. More than 30000 oysters sample collected by quantitative survey were applied to analyze the oyster assemblages.ResultsThe analyses revealed 12 mitochondrial lineages representing three genera within the family Ostreidae. Phylogenetic analysis confirmed robust monophyletic groupings, confirming species identities and leading to the identification of two cryptic species within the genus Saccostrea. Based on DNA evidence, these two cryptic Saccostrea species were closely related to the known S. non-mordax D and H lineages. Quantitative analysis showed that Crassostrea sikamea was the most prevalent species in the study area, with an average abundance and biomass > 1,400 individuals/m2 and 4,449 grams/m2, respectively. Qualitative and quantitative assessment both revealed at least 6 species were identified at G07 (Jieyang), being the most biodiverse location of Guangdong Province.DiscussionBy mapping oyster distribution and updating the species inventory, our study provides a foundation for future research on oyster populations and informs conservation efforts aimed at preserving and restoring oyster habitats, thereby supporting marine biodiversity.